Matriosche: nonne, madri e nipoti. Tre esempi di genealogie femminili nella letteratura italiana del ovecento - Daniele Cerrato (Studia Romanica Posnaniensia, 2018)
Starting from the myth, culture and society have always opposed the construction of a matriarchal lineand a genealogy of women. The paper address the generational relationships between women, and focuses on three novel Italian Novecento women writers: Susanna Tamaro, Michela Murgia and Milena Agus. Tamaro, Murgia and Agus conform an atypical female genealogy in their novels, and propose new models of identity in opposition to the patriarchal system.